Review of quinoa fermentation: product diversity, process optimization, and nutritional enhancement - Li, Chen; Liu, Tong; Li, Xiaohong; Gao, Wenli; Lv, Jiayin; Hu, Gaojian; Li, Chunjiang; Liu, Fangfang; Liu, Xianjun; Meng, Xianglong (Frontiers in Nutrition, 2025)
Fermented quinoa has emerged as a promising functional food owing to its enhanced nutritional profile, improved bioactive compound bioavailability, and favorable sensory attributes. Key fermentation parameters-microbial selection, process conditions, and substrate pretreatment-that govern the quality and functionality of fermented quinoa products. It highlights microbial-driven biotransformation of polyphenols and flavonoids, which enhances antioxidant activity and bioavailability. Fermentation also modulates sensory profiles and promotes gut health through enrichment of beneficial genera. These data provide a foundational framework for process standardization, scale-up, and industrial adaptation, particularly highlighting the versatility of lactic acid bacteria and the need for mechanized fermentation technologies to enhance commercial viability. Future research should focus on multi-omics approaches to decipher microbial consortia dynamics, in vivo validation of health benefits, development of clean-label formulations, and exploration of sustainable fermentation technologies. This review provides a scientific foundation for optimizing quinoa-based biotransformation processes and accelerating the development of next-generation fermented quinoa products with enhanced nutritional and health-promoting properties.